Pathologic Description and Genetic Characterisation of Kudoa thunni From Yellowfin Tuna ( Thunnus albacares ) in the Caribbean Sea - Noor‐Ul Huda; Magali Duran; Jonnel Edwards; Cynthia Ware; Olando Harvey; Matt J. Griffin; David P. Marancik (Journal of Fish Diseases, 2026)
Yellowfin tuna ( Thunnus albacares ) is a valuable recreational and commercial species in Grenada and the Caribbean region. Myxozoans, specifically the monotypic Kudoidae family within the Order Multivalvulida, are marine parasitic organisms that can negatively impact fish health and marketability. On 8 September 2023, muscle fillets from a yellowfin tuna caught off the coast of Grenada and containing numerous white nodules were submitted for diagnostic evaluation. Gross examination of the muscle showed firm, spherical to ovoid, white polysporous cysts approx. 0.8–1.3 mm in diameter and approx. 10–20 cysts per 2 × 2 cm section of muscle. Cysts were sharply excised and assessed by wet mount cytology revealing a myriad of quadrate myxosporean parasites consistent with the genus Kudoa . Histopathologic examination demonstrated numerous, intracytoplasmic plasmodia with thick hyaline walls containing intact and necrotic myxospores. Parasites present outside of plasmodia were associated with myoliquifaction of the tissue. The case isolate was morphologically consistent with K. thunni and the partial 18S small subunit rDNA (SSU) and 28S large subunit rDNA (LSU) demonstrated high homology (SSU: 99.8%–100%; LSU: 99.5%–100%) to several K. thunni isolates, including those isolated from blackfin tuna ( T. atlanticus ) harvested near the Caribbean islands of St. Kitts and Nevis. This is the first report of K. thunni infecting yellowfin tuna in the Caribbean region and expands the epidemiologic, pathologic, and molecular record for this parasite.